Transrectal ultrasonography versus digitally guided prostate biopsies in patients with palpable lesions on digital rectal examination - (:unkn) unknown (My University, 1995)
OBJECTIVE: To compare the efficacy of digital and ultrasonographic guidance of biopsies when there is a palpable lesion on the prostate. PATIENTS AND METHODS: Forty patients with a palpable nodule confined to a single lobe of the prostate underwent digitally guided biopsies of this lesion or biopsies directed by transrectal ultrasonography (TRUS) and/or systematic biopsies. RESULTS: According to the histopathological examination, 21 patients were found to have prostate carcinoma (PCa) using TRUS-guided biopsies, whereas digitally guided biopsies revealed PCa in 18 patients but did not detect three cases. In the study group, the prostate of 10 patients had a normal ultrasonographic appearance and two patients had PCa revealed by systematic biopsies. CONCLUSION: We suggest that in the presence of a palpable lesion in the prostate, regardless of TRUS findings, systematic biopsies are mandatory. Present data indicates that digitally guided biopsies are unnecessary as they do not provide additional information over systematic or TRUS-guided biopsies.
Keywords: Humans; Middle Aged; Aged; Male; Prostatic Neoplasms; Prospective Studies; Biopsy, Needle; Prostate-Specific Antigen; Ultrasonography, Interventional; Diagnosis, Computer-Assisted; Palpation